Penerapan Logika Fuzzy untuk Penentuan Penerima Sembako Murah di Perumahan Cipta Green View RT 11 RW 21, Batam - Chan, Andi Supriyadi; Aranski, Alvendo (JURNAL SITEBA, 2022)
The distribution of subsidized basic necessities (sembako) is one of the government's programs to assist low-income communities. However, determining the recipients of subsidized sembako often faces challenges in terms of objectivity and accuracy. This study aims to develop a system for determining recipients of subsidized sembako using the fuzzy logic method in Cipta Green View Housing RT 11 RW 21, Batam. The method used is Fuzzy Mamdani with input variables including income, number of dependents, and housing conditions. The results show that the fuzzy logic system is able to provide recommendations for subsidized sembako recipients with an accuracy rate of 85% compared to manual assessment. This system is expected to improve the effectiveness and transparency of the subsidized sembako distribution program.